Political Influences On Accounting Standards: A Discussion Of GAAP & IFRS - KALUNDU KIMANZI; ROBERT ODEK (Accounting and Finance Studies, 2023)
Accounting standards, as expressions of public policy, are not constantly impartial in that they inflict benefits on some individuals in society to the disadvantage of others. This has been as a result of the power play between the US GAAP and the proponents of IFRS. This paper presents the political factors affecting the accounting standard setting. The paper discusses the debate between the adoption of accounting principles (IFRS) or accounting rules (GAAP). It presents the convergence of accounting standards and the future of IFRS.